Pengaruh struktur modal, etnis dewan komisaris dan kebijakan dividen dengan profitabilitas sebagai variabel kontrol terhadap nilai perusahaan - Rahma, Anita Ade; Bawamenewi, Desberatus (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2018)
This study aims to determine the effect of capital structure, ethnic board of commissioners and dividend policy on Company Value in manufacturing companies listed on the Indonesia Stock Exchange. By taking secondary data that has been published in the 2015-2017 period. Population of 164 in manufacturing companies listed on the Indonesia Stock Exchange 2015-2017 and 112 samples of companies using purposive sampling with a total of 336 company annual data observations. The results of this study concluded that the Capital Structure and Ethnicity of the Board of Commissioners had no effect and were not significant to the Company's Value. Dividend Policy has a positive and significant effect on Company Value. Profitability has no effect and is not significant on Company Value. This means that with the capital structure, ethnic board of commissioners and dividend policy will encourage a more optimal level of supervision of the quality of the company. The company's objectives are achieved if the company's performance is able to optimize the company's value. Especially by better managing the dividend policy because it is considered capable of increasing the value of the company which has a direct impact on the company's sustainability in the future.Keywords: Institutional ownership; tax planning; foreign board of commissioners; leverage;Â the company value.